Factors Affecting the Accounting Estimate of Provision for Devaluation of Inventories - Huong Thi Thu Bui; Van Thi Hong Nguyen; Cham Thi Quynh Nguyen (Universitas Pasundan, 2023)
To improve the quality of accounting estimates of provision for devaluation of inventories, it is necessary to study the factors that affect the accounting estimates of provision for devaluation of inventories in enterprises. Thus, there are solutions to overcome the limitations in accounting estimates of provision for the devaluation of inventories. This study was conducted to determine the factors affecting the accounting estimate of provision for the devaluation of inventories. The study is based on data from 60 companies operating in the field of building materials for the period 2019-2021 in Vietnam. Panel data analysis was used in this study. The results of panel data analysis show that firm size, inventory, and audit unit have a positive impact on the ability to make provision for devaluation of inventories. In addition, the study did not find the effect of profitability ratio and type of state ownership on inventory provisioning. Based on the results of this study, the authors also make some implications for companies as well as external auditors. The value of the research will help prepare for the devaluation of inventories. Factors for predicting provision for devaluation of inventories are also included in this study.